Crosslinking‐Induced White Light Emission of Poly(Hydroxyurethane) Microspheres for White LEDs. Issue 14 (24th February 2020) - Liu, Bin; Chu, Bo; Wang, Ya‐Ling; Chen, Zheng; Zhang, Xing‐Hong
Abstract: Nonconjugated luminescent polymers with white light emission are promising for a wide range of applications in display and lighting devices, but their preparation remains a big challenge. Herein, a white‐light‐emitting nonconjugated poly(hydroxyurethane) microsphere (PHUM) synthesized from the crosslinking reaction of trimethylolpropane tri(cyclic carbonate) ether and 1, 6‐hexanediamine in chloroform is reported. The resultant PHUMs possess uniform sizes ranging from 12.6 to 21.5 µm. It is proposed that a high crosslinking degree and various hydrogen‐bonding strengths induce the formation of carbamate clusters with different sizes and broad distributions, which result in a broad emission spectrum. The cluster‐size distribution effect leads to multiple n –π* transitions from various carbamate clusters via through‐space conjugation of carbamates, realizing white light emission. In addition, the application of PHUMs as single phosphor combined with a 365 nm UV chip is also demonstrated, with which a white‐light‐emitting diode with a high color rendering index of up to 95 is obtained. This work confirms that crosslinking can induce multiple emissions, which provides a new clusteroluminescence and polymerization‐induced emission system for tunable luminescence emission. Abstract : Crosslinking‐induced cluster‐size distribution in poly(hydroxyurethane) microspheres (PHUMs) leads to multiple n –π* transitions of various carbamate clusters via through‐space conjugation of carbamates, realizing white light emission. A white light‐emitting diode with a color rendering index as high as 95 is achieved when PHUMs‐180 (prepared at 180 °C) are applied as single phosphor combined with a UV chip.